Overnight Company I plant design coconut oil extraction conventional dry process - Cheng, Sui Soan S. (College of Engineering, 1977)
Plant: integrated coconut plant -- Site: Zamboanga City -- Plant site area: 8,064 sq. m. -- Main raw material: coconut -- Secondary raw materials: 20°Be caustic soda, fullers earth -- Plant operation: 24 hrs/day at 360 days/year -- Plant capacity: 4,292 tons/year -- Fixed capital: P 4,987,500.00 -- Annual total cost: P 21,519,480.00 -- Annual sales: P 24,709,378.00 -- Gross profit: P 3,189,898.00 -- Net income: P 2,392,423.50 -- Per cent rate of return (based on fixed capital): 38% -- Break-even point: 33% -- Shut-down point: 23% -- Pay-out time: 2.63 years